Polyimide film and method for producing the same

By using a polyamic acid composition with controlled storage conditions, the microbubble defects in polyimide films are minimized, enhancing the film's suitability for fine pattern formation in flexible electronic devices.

JP7605248B2Active Publication Date: 2024-12-24TOYOBO CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023090242
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2024-12-24
Estimated Expiration
2039-01-23

AI Technical Summary

Technical Problem

Polyimide films used as substrates for flexible electronic devices often exhibit microbubbles and surface defects that are difficult to detect with normal optical microscopes but cause unevenness and reduce the accuracy of fine pattern formation in photolithography processes.

Method used

The use of a polyamic acid composition containing specific fatty acid compounds with 8 to 30 carbon atoms, stored in containers with inner walls made of polymeric materials with a glass transition temperature of 40°C or lower, and controlled storage conditions to minimize microbubble formation.

Benefits of technology

Reduces the number of defects visible under a differential interference microscope to 2 defects/cm² or less, ensuring high-quality polyimide films suitable for fine pattern formation in flexible electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605248000002
    Figure 0007605248000002
  • Figure 0007605248000001
    Figure 0007605248000001
Patent Text Reader

Abstract

To provide a polyimide film useful as a substrate for backplane of a flexible display requiring fine TFT formation.SOLUTION: A high-quality polyimide film having the number of micro-defects observable only by a differential interference microscope of 2 / sq.cm or less is obtained via a process of forming a composition at least contains aromatic tetracarboxylic acid, polyamic acid obtained from diamine and organic solvent, which is a polyamic acid composition having the content of one or more kinds of compound at least selected from fatty acid with a carbon number 8 to 30, fatty acid salt with a carbon number 8 to 30, fatty acid amide with a carbon number 8 to 30 and fatty acid derivative with a carbon number 8 to 30 to the polyamic acid is 0.05 mass% or less, into a film shape; and a process of performing heating treatment at the temperature of 350°C or more and 550°C or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide film having few defects and a smooth surface suitable for forming fine thin film elements, and further to a polyimide film suitable for use as a substrate for flexible electronic devices. [Background technology]

[0002] The present inventors have conducted intensive research to provide a polyimide film that can be suitably used as a substrate for flexible electronic devices, and have developed a polyimide film having a novel chemical structure with a benzoxazole skeleton, as shown in Patent Documents 1 to 4, for example. Such a polyimide film exhibits an extremely low linear expansion coefficient, high heat resistance, and low thermal shrinkage, and can be suitably used as a substrate for fine semiconductor devices and the like. For example, as shown in Patent Documents 5 to 7, it can be applied as a substrate for semiconductor devices or a substrate for display elements. Furthermore, as shown in Patent Document 8, the present inventors have developed a process in which a polyimide film is temporarily supported by bonding it to an inorganic substrate such as glass, and then a fine device is formed on the film surface, followed by peeling it off from the inorganic substrate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 3858892 [Patent Document 2] Patent No. 3937235 [Patent Document 3] Patent No. 3953057 [Patent Document 4] Patent No. 3956940 [Patent Document 5] Patent No. 3761030 [Patent Document 6] Patent No. 3783870 [Patent Document 7] Patent No. 4131412 [Patent Document 8] Patent No. 5796292 Summary of the Invention [Problem to be solved by the invention]

[0004] In the course of the above development, the inventors encountered a phenomenon in which a film surface had a very slight uneven defect with a gentle curvature. This type of defect is difficult to find in a magnified observation of the outermost surface using a normal optical microscope because the unevenness is gentle, but can be observed using a differential interference microscope, which can obtain a strong contrast. The inventors closely observed the inside of the film at the defective portion, the position of which was identified using a differential interference microscope, and found that microbubbles had been generated inside the film. The inventors thoroughly analyzed the microbubbles generated inside the polyimide film and the surrounding area, but were unable to find any traces that could be the source of the microbubbles, making the generation of such defects very puzzling. [Means for solving the problem]

[0005] Means for Solving the Problems The present inventors have conducted extensive research to find a solution to the above problems, and as a result have discovered that the cause of the microbubbles lies in the polyamic acid composition, which is a precursor for producing a polyimide film, and in the raw material monomers and solvents for producing the polyamic acid composition, and have further discovered a method for eliminating this cause.

[0006] That is, the present invention has the following configuration. [1] A polyimide film characterized in that the number of defects with a diameter of 2 μm or more observed using a differential interference contrast microscope is 2 or less per square centimeter. [2] The polyimide film according to [1], wherein the defect portion having a diameter of 2 μm or more observed by the differential interference microscope is a convex defect resulting from a cavity having an outer diameter size of 0.5 μm or more and 5 μm or less in the film surface direction that exists inside the film at the same planar coordinate position. [3] The polyimide film according to [1] or [2], characterized in that the outer diameter size of the cavity, as determined by cross-sectional observation of the film in the thickness direction of the film, is 0.1 μm or more and 3 μm or less. [4] A method for producing a polyimide film according to any one of [1] to [3], comprising at least a step of forming a polyamic acid composition comprising at least a polyamic acid obtained from an aromatic tetracarboxylic acid and a diamine and an organic solvent, the polyamic acid having a total content of a fatty acid having 8 to 30 carbon atoms, a fatty acid salt having 8 to 30 carbon atoms, a fatty acid amide having 8 to 30 carbon atoms, and a fatty acid derivative having 8 to 30 carbon atoms of 0.05 mass% or less into a film shape, and then a step of heat-treating the polyamic acid at a temperature of 350°C or more and 550°C or less.

[0007] Furthermore, the present invention preferably has the following configuration. [5] A method for producing a polyimide film according to any one of [1] to [3], comprising at least a step of obtaining a polyamic acid composition comprising at least a polyamic acid obtained from an aromatic tetracarboxylic acid and a diamine and an organic solvent, the polyamic acid having a total content of a fatty acid having 8 to 30 carbon atoms, a fatty acid salt having 8 to 30 carbon atoms, a fatty acid amide having 8 to 30 carbon atoms, and a fatty acid derivative having 8 to 30 carbon atoms of 0.05 mass% or less based on the polyamic acid, and a step of obtaining a polyimide film using the polyamic acid composition. [6] At least a part of the inner wall is placed in a container made of a polymer material with a glass transition temperature of 40°C or less. log 10 (day)≦2300×(1 / T)-5.3 (Here, day is the storage time (unit: day), and T is the storage temperature (unit: K).) The method for producing the polyamic acid composition according to [5], wherein the aromatic tetracarboxylic acid is used as a polymerization raw material after being stored within a storage temperature and storage time range that satisfies the following relational expression: [7] At least a part of the inner wall is placed in a container made of a polymer material with a glass transition temperature of 40°C or less. log 10(day)≦2300×(1 / T)-5.3 (Here, day is the storage time (unit: day), and T is the storage temperature (unit: K).) The method for producing the polyamic acid composition according to [5], wherein the diamine is stored within a storage temperature and storage time range that satisfies the following relational expression and then used as a polymerization raw material. [8] At least a part of the inner wall is placed in a container made of a polymer material with a glass transition temperature of 40°C or less. log 10 (day)≦2300×(1 / T)-5.3 (Here, day is the storage time (unit: day), and T is the storage temperature (unit: K).) The method for producing the polyamic acid composition according to [5], wherein the organic solvent is used as a polymerization solvent after storage within a storage temperature and storage time range that satisfies the following relational expression: [9] At least a part of the inner wall is placed in a container made of a polymer material with a glass transition temperature of 40°C or less. log 10 (day)≦2300×(1 / T)-5.3 (Here, day is the storage time (unit: day), and T is the storage temperature (unit: K).) and mixing the inorganic particles in a solvent dispersion after storage within a storage temperature and storage time range that satisfies the relational expression below with a polymerization raw material.

[10] A method for producing the polyimide film according to any one of [1] to [3], comprising at least a step of obtaining the polyamic acid composition according to any one of [5] to [9], characterized in that the polymeric material constituting a part of the inner wall of the container contains 0.05 to 5 mass % of one or more compounds selected from the group consisting of fatty acids having 8 to 30 carbon atoms, fatty acid salts having 8 to 30 carbon atoms, and fatty acid derivatives having 8 to 30 carbon atoms, and a step of obtaining a polyimide film using the polyamic acid composition.

[11] The method for producing a polyimide according to any one of [5] to

[10] , wherein the polyamic acid composition is heat-treated at a temperature of at least 350° C. and not more than 550° C. Effect of the Invention

[0008] First, the defects that this invention deals with are defects found when observing the surface of a polyimide film with a differential interference microscope. A differential interference microscope is a type of phase contrast microscope that uses overlapping observation lights with different phase differences to observe the difference in refractive index of the observed object or the interference of light caused by fine unevenness. By using a differential interference microscope, it is possible to observe the internal structure of a transparent observed object, as well as extremely gentle steps and unevenness, with high contrast. As mentioned above, the inventors have confirmed the presence of extremely small microscopic bubbles inside the film at the locations corresponding to the defects addressed in this application, and believe that such microscopic bubbles inside the film form unevenness with extremely gradual steps on the film surface, which are the cause of the defects.

[0009] The present inventors have discovered that microbubbles are generated when one or more compounds (hereinafter referred to as causative compounds) selected from fatty acids having 8 to 30 carbon atoms, fatty acid salts having 8 to 30 carbon atoms, fatty acid amides having 8 to 30 carbon atoms, and fatty acid derivatives having 8 to 30 carbon atoms are detected in a polyamic acid composition. Furthermore, the origin of the causative compounds that cause these microbubbles was investigated, and it was found that they originate mainly from the materials used in the inner walls of containers that contain the raw materials of the polyamic acid composition, such as tetracarboxylic anhydride, diamine, and solvent. That is, the causative compounds were additives such as solid lubricants, modifiers, plasticizers, and stabilizers added to the materials of the plastic containers, the inner layer materials of metal cans, and even the materials inside the storage bags, i.e., sealant resins, or oligomer components. The materials of the inner walls of such containers and sealant resins are polymer materials with relatively low glass transition temperatures. In such relatively low molecular weight polymer materials, the additives mentioned above are used to stably supply the products. In addition, it is difficult to reduce the oligomer components to zero in terms of probability if the polymer material is used. However, after extensive research, the inventors have found that when the glass transition temperature of the polymeric material used for the inner wall of a container is 40°C or lower, the intrusion of the causative compound can be kept to a minimum even when the container is used and the safety temperature is properly controlled. That is, by storing a polyamic acid composition, which is a precursor of a polyimide film, or its raw materials such as monomers and solvents in a container whose inner wall is coated with a polymeric material having a glass transition temperature of 40°C or less and storing the container at a temperature of 40°C or less, it is possible to suppress the amount of the causative compound mixed into the polyamic acid to a level below which microbubbles become apparent.

[0010] Surface irregularities that are difficult to detect without a differential interference microscope have not been a particular problem in general flexible printed circuit boards, COF, TAB, etc. However, in TFT processing, which requires extremely fine pattern processing by photolithography, such as the backplane of a flexible display, even submicron-order steps reduce the accuracy of pattern formation by exposure, so it is extremely important to reduce such defects. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a graph showing the results of a storage experiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The polyimide of the present invention is a polymer formed by imide bonds. Generally, polyimide is obtained as a condensation product of tetracarboxylic dianhydride and diamine. A common method for producing polyimide is to apply an organic solvent solution (also called a polyamic acid composition) of polyamic acid (polyimide precursor) obtained by reacting tetracarboxylic dianhydride with diamine in a solvent to a support, dry the solution to form a precursor film, and convert the film into polyimide by heating or by the action of a catalyst. When forming a polyimide film, a method of peeling the precursor film from the support and imidizing the film is common. In addition, a method of imidizing the film without peeling the film is also known for applications in which the support is covered. The method of applying a precursor solution to a support such as a glass substrate and drying the solution to form the polyimide on the support is being considered for practical use in applications in which the polyimide film is used as a substrate for flexible devices.

[0013] As the tetracarboxylic dianhydride of the present invention, aromatic tetracarboxylic dianhydrides and alicyclic tetracarboxylic dianhydrides can be preferably used. From the viewpoint of heat resistance, aromatic tetracarboxylic dianhydrides are preferred, and from the viewpoint of light transmittance, alicyclic tetracarboxylic dianhydrides are preferred. The tetracarboxylic dianhydrides may be used alone or in combination of two or more kinds.

[0014] Examples of the aromatic tetracarboxylic acid of the present invention include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propanoic anhydride, etc. In the present invention, the use of pyromellitic dianhydride is preferred.

[0015] Examples of the alicyclic tetracarboxylic acids of the present invention include alicyclic tetracarboxylic acids such as cyclobutane tetracarboxylic acid, 1,2,4,5-cyclohexane tetracarboxylic acid, and 3,3',4,4'-bicyclohexyl tetracarboxylic acid, and their acid anhydrides. Among these, dianhydrides having two anhydride structures (e.g., cyclobutane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, and 3,3',4,4'-bicyclohexyl tetracarboxylic dianhydride) are preferred. The alicyclic tetracarboxylic acids may be used alone or in combination of two or more. When transparency is important, the alicyclic tetracarboxylic acids preferably account for, for example, 80 mass % or more of the total tetracarboxylic acids, more preferably 90 mass % or more, and further preferably 95 mass % or more.

[0016] The diamines of the present invention are not particularly limited, and aromatic diamines, aliphatic diamines, alicyclic diamines, etc., which are usually used in polyimide synthesis, can be used. From the viewpoint of heat resistance, aromatic diamines are preferred, and among aromatic diamines, aromatic diamines having a benzoxazole structure can be used. When aromatic diamines having a benzoxazole structure are used, it is possible to develop high heat resistance, high elastic modulus, low thermal shrinkage, and low linear expansion coefficient. The diamines may be used alone or in combination of two or more kinds.

[0017] Among the diamines of the present invention, examples of aromatic diamines include 2,2'-dimethyl-4,4'-diaminobiphenyl, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene (bisaniline), 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, bis[4-(3-aminophenoxy)phenyl]ketone ... 2,2-bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, m-aminobenzylamine, p-aminobenzylamine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether ter, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 3,4'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diaminodiphenyl methane, 3,4'-diaminodiphenyl methane, 4,4'-diaminodiphenyl methane bis[4-(4-aminophenoxy)phenyl]ethane, bis[4-(4-aminophenoxy)phenyl]ethane, bis[4-(4-aminophenoxy)phenyl]ethane, bis[4-(4-aminophenoxy)phenyl]ethane, bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]butane,3-bis[4-(4-aminophenoxy)phenyl]butane, 1,4-bis[4-(4-aminophenoxy)phenyl]butane, 2,2-bis[4-(4-aminophenoxy)phenyl]butane, 2,3-bis[4-(4-aminophenoxy)phenyl]butane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3-methylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3-methylphenyl]propane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)phenyl] 1,4-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy) phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfoxide, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, 1,3-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(3-aminophenoxy)benzoyl]benzene, 4,4'-bis[(3-aminophenoxy)benzoyl]benzene, 1 ,1-Bis[4-(3-aminophenoxy)phenyl]propane, 1,3-Bis[4-(3-aminophenoxy)phenyl]propane, 3,4'-diaminodiphenyl sulfide, 2,2-Bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, bis[4-(3-aminophenoxy)phenyl]methane, 1,1-Bis[4-(3-aminophenoxy)phenyl]ethane, 1,2-Bis[4-(3-aminophenoxy)phenyl]ethane, bis[4-(3-aminophenoxy)phenyl]sulfoxide, 4,4'-bis[3-(4-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[3-(3-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzophenone, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]diphenyl sulfone, bis[4-{4-(4-aminophenoxy)phenoxy}phenyl]sulfone, 1,4-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1, 3-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-fluorophenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-methylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-cyanophenoxy)-α,α-dimethylbenzyl]benzene, 3,3'-diamino-4,4 '-Diphenoxybenzophenone, 4,4'-diamino-5,5'-phenoxybenzophenone, 3,4'-diamino-4,5'-diphenoxybenzophenone, 3,3'-diamino-4-phenoxybenzophenone, 4,4'-diamino-5-phenoxybenzophenone, 3,4'-diamino-4-phenoxybenzophenone, 3,4'-diamino-5'-phenoxybenzophenone, 3,3'-diamino-4,4'-dibiphenoxybenzophenone, 4,4'-diamino-5,5'-dibiphenoxybenzophenone, 3,4'-diamino-4,5 '-Diamino-4-biphenoxybenzophenone, 3,3'-diamino-4-biphenoxybenzophenone, 4,4'-diamino-5-biphenoxybenzophenone, 3,4'-diamino-4-biphenoxybenzophenone, 3,4'-diamino-5'-biphenoxybenzophenone, 1,3-bis(3-amino-4-phenoxybenzoyl)benzene, 1,4-bis(3-amino-4-phenoxybenzoyl)benzene, 1,3-bis(4-amino-5-phenoxybenzoyl)benzene, 1,4-bis(4-amino-5-phenoxybenzoyl)benzene, 1,Examples of the aromatic diamines include 3-bis(3-amino-4-biphenoxybenzoyl)benzene, 1,4-bis(3-amino-4-biphenoxybenzoyl)benzene, 1,3-bis(4-amino-5-biphenoxybenzoyl)benzene, 1,4-bis(4-amino-5-biphenoxybenzoyl)benzene, 2,6-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzonitrile, and aromatic diamines in which some or all of the hydrogen atoms on the aromatic ring of the aromatic diamine are substituted with halogen atoms, alkyl or alkoxy groups having 1 to 3 carbon atoms, cyano groups, or halogenated alkyl or alkoxy groups having 1 to 3 carbon atoms in which some or all of the hydrogen atoms of the alkyl or alkoxy groups are substituted with halogen atoms.

[0018] Examples of the aliphatic diamines of the present invention include 1,2-diaminoethane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, and 1,8-diaminooctane. Examples of the alicyclic diamines of the present invention include 1,4-diaminocyclohexane, 4,4'-methylenebis(2,6-dimethylcyclohexylamine), and the like.

[0019] Examples of the diamines having a benzoxazole structure of the present invention include 5-amino-2-(p-aminophenyl)benzoxazole, 6-amino-2-(p-aminophenyl)benzoxazole, 5-amino-2-(m-aminophenyl)benzoxazole, 6-amino-2-(m-aminophenyl)benzoxazole, 2,2'-p-phenylenebis(5-aminobenzoxazole), 2,2'-p-phenylenebis(6-aminobenzoxazole), 1-(5-aminobenzoxazolo)-4-(6-aminobenzoxazolo)benzene, 2,6-(4,4'-diaminodiphenyl)benzoxazole, 1-(5-aminobenzoxazolo)-4-(6-aminobenzoxazolo)benzene ... 2,6-(4,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, and the like.

[0020] In the present invention, the polyimide preferably used is a film made of a condensation product of an aromatic tetracarboxylic dianhydride and an aromatic diamine, and further, (a) a film of a condensation product of an aromatic tetracarboxylic dianhydride and a diamine including at least a diamine having a benzoxazole skeleton; (b) a film of a condensation product of an aromatic tetracarboxylic dianhydride and a diamine containing at least a diamine having an ether bond in the molecule; (c) a film of a condensation product of an aromatic tetracarboxylic dianhydride and a diamine including at least phenylenediamine; and (d) a film of a condensation product of biphenyltetracarboxylic dianhydride and an aromatic diamine.

[0021] The thickness of the polyimide film of the present invention is not particularly limited, but is preferably 0.5 μm to 200 μm, and more preferably 3 μm to 50 μm. If the thickness is less than 0.5 μm, it is difficult to control the film thickness, and there is a possibility that some polyimide may be missing. This may cause difficulty in peeling off the second polyimide layer. On the other hand, if the thickness is more than 200 μm, it may take a long time to prepare the film, and it may be difficult to control the unevenness in the film thickness. It is essential that the unevenness in the film thickness of the polyimide layer is 5% or less, more preferably 4% or less, and even more preferably 3% or less.

[0022] The film of the condensate of the tetracarboxylic dianhydride and the diamine of the present invention, i.e., the polyimide film, can be obtained by a solution film forming method. The solution film forming method of polyimide is a method in which a stainless steel roll or an endless belt, or a polymer film such as PET, is used as a long or endless support, a precursor solution of a polyimide resin is applied onto the support, and after drying, the support is peeled off to obtain a polyimide precursor film, and the film is preferably held at both ends with clips or pins and conveyed while being further heat-treated to chemically react the polyimide precursor into polyimide to obtain a polyimide film. The polyimide film obtained by this method has a thickness unevenness of 5% or less, preferably 3.6% or less, more preferably 2.4% or less, and a tensile breaking strength of 90 MPa or more, preferably 180 MPa or more, more preferably 350 MPa or more, and even more preferably 450 MPa or more.

[0023] In the present invention, it is possible to add inorganic substances to polyimide in order to adjust the properties of the polyimide layer, but the amount should be kept to a minimum. In general, when polymers are made into a film, a small amount of inorganic particles called lubricants is added to actively generate minute convexities on the film surface, and when a film is overlapped with another film or a film with a smooth surface, an air layer is trapped between them, thereby making the film slippery. In the present invention, it is preferable to keep the silicon oxide component contained in the polyimide layer to 6000 ppm or less, preferably 4500 ppm or less, more preferably 1800 ppm or less, and even more preferably 900 ppm or less. Addition of an excessive amount of lubricant may increase the roughness of the film surface and inhibit the peelability of the second polyimide layer. Such inorganic particles are often transferred to the polyamic acid composition in a state of being dispersed in an organic solvent or the like.

[0024] In the present invention, the outer diameter of a defect or microbubble is the diameter if it is circular or spherical, and is the diameter of the circumscribing circle if it is distorted or irregular in shape. The diameter of the circumscribing circle can be relatively easily determined by image processing, etc., if a clear image is available.

[0025] The polyamic acid composition of the present invention includes an organic solvent solution of polyamic acid and a polyamic acid film (also called GF: gel film or green film) obtained by drying the organic solvent of polyamic acid. Although it is called a polyamic acid film for convenience, when a polyamic acid solution is actually applied to a support and dried, imidization by dehydration condensation reaction proceeds in part of the polyamic acid at the same time as drying, resulting in a state in which polyamic acid, polyimide, and the organic solvent coexist. In the present invention, the content of at least one compound (hereinafter referred to as fatty acid compound) selected from fatty acids having 8 to 30 carbon atoms, fatty acid salts having 8 to 30 carbon atoms, fatty acid amides having 8 to 30 carbon atoms, and fatty acid derivatives having 8 to 30 carbon atoms in the polyamic acid composition is specified. However, since the amount of polyamic acid present varies depending on the polyimidization process as described above, in the present invention, "relative to the mass of polyamic acid" refers to the total amount of tetracarboxylic acid and diamine, which are raw materials for polyamic acid.

[0026] The present invention is characterized in that a polyimide is obtained by using a polyamic acid composition, which is a precursor of a polyimide, and which contains one or more compounds selected from fatty acids having 8 to 30 carbon atoms, fatty acid salts having 8 to 30 carbon atoms, fatty acid amides having 8 to 30 carbon atoms, and fatty acid derivatives having 8 to 30 carbon atoms, in an amount of 0.1 mass% or less based on the mass of the polyamic acid.

[0027] The fatty acid having 8 to 30 carbon atoms in the present invention may be either a saturated fatty acid or an unsaturated fatty acid, and examples thereof include octanoic acid, caprylic acid, nonanoic acid, pelargonic acid, dodecanoic acid, lauric acid, tetradecanoic acid, myristic acid, pentadecanoic acid, pentadecylic acid, hexadecanoic acid, palmitic acid, 9-hexadecenoic acid, palmitoleic acid, heptadecanoic acid, margaric acid, octadecanoic acid, stearic acid, cis-9-octadecenoic acid, oleic acid, 11-octadecenoic acid, vaccenic acid, cis,cis-9,12-octadecadienoic acid, linoleic acid, 9,12,15-octadecanetrienoic acid, (9,12,15)-linolenic acid, 6, These include 9,12-octadecatrienoic acid, (6,9,12)-linolenic acid, 9,11,13-octadecatrienoic acid, eleostearic acid, eicosanoic acid, arachidic acid, 8,11-eicosadienoic acid, 5,8,11-eicosatrienoic acid, mead acid, 5,8,11-eicosatetraenoic acid, arachidonic acid, docosanoic acid, behenic acid, tetracosanoic acid, lignoceric acid, cis-15-tetracosanoic acid, nervonic acid, hexacosanoic acid, cerotic acid, octacosanoic acid, montanic acid, triacontanoic acid, melissic acid, erucic acid, nervonic acid, arachidonic acid, eicosatetraenoic acid, docosapentaenoic acid, and docosahexaenoic acid.

[0028] The fatty acid salts having 8 to 30 carbon atoms in the present invention include alkali metal salts, ammonium salts, divalent metal salts, trivalent metal salts, tetravalent metal salts, and the like of the fatty acids exemplified above.

[0029] Representative examples of the fatty acid amides having 8 to 30 carbon atoms according to the present invention are compounds obtained by the dehydration condensation reaction of the above-mentioned fatty acids and ammonia, and are also called fatty amides. Examples of fatty acid amides include stearic acid amide, oleic acid amide, erucic acid amide, methylene bis stearic acid amide, and ethylene bis stearic acid amide.

[0030] The fatty acid derivatives having 8 to 30 carbon atoms according to the present invention include esters of the above-mentioned fatty acids, halogen-substituted products, and polymers derived from unsaturated bonds. In the present invention, the content of one or more compounds (fatty acid compounds) selected from the group consisting of fatty acids having 8 to 30 carbon atoms, fatty acid salts having 8 to 30 carbon atoms, fatty acid amides having 8 to 30 carbon atoms, and fatty acid derivatives having 8 to 30 carbon atoms is 0.1% by mass or less, preferably 0.01% by mass, and more preferably 0.003% by mass, based on the mass of polyamic acid in the polyamic acid composition. The lower limit is not particularly set, as it is below the lower detection limit.

[0031] These fatty acid compounds exist in a very small amount in the solvent of the polyamic acid composition, but because they are inherently poorly compatible with the solvent of the polyamic acid composition, as the drying progresses and the amount of the solvent decreases, they reach a concentration relatively higher than the solubility, and precipitate to form fine particles or micelles in the composition. That is, these fine particles or micelles are generated in the polyamic acid film, and then thermally decomposed or sublimated during the heat treatment to dehydrate and condense the polyamic acid to imidize it, thereby generating fine bubbles. If the amount of these fatty acid compounds is within a predetermined range, the temperature is high enough when the concentration at which fine particles or micellization occurs is reached, and the compounds decompose or sublimate before precipitating in the form of fine particles or micelles, so that fine bubbles are not generated.

[0032] The inventors have investigated the origin of these fatty acid compounds and found that they originate from the containers used to store the raw materials of polyamic acid or the polyamic acid solution. That is, these fatty acid compounds accumulate by migrating from the materials used for the inner walls of the containers to the raw materials or the polyamic acid solution during storage. These fatty acid compounds are relatively chemically stable, so they do not directly inhibit the polymerization reaction of polyamic acid or the dehydration reaction when polyamic acid is converted to polyimide, and are therefore easily overlooked.

[0033] Examples of containers for storing the raw material of polyamic acid, the solvent, the polyamic acid composition, etc. used in the present invention are 18L cans and small metal cans. The inner walls of these metal containers are laminated with a polyethylene film, a propylene film, a polyolefin film, a vinyl fluoride film, a polyester film, etc., to prevent direct contact between the contents and the metal. In addition, the lids often use a similar relatively flexible resin as a sealer. Another example of the container for storing the polyamic acid raw material, the solvent, the polyamic acid composition, etc. used in the present invention is a so-called plastic container, which is made of a relatively flexible polymeric material having high chemical stability, such as polyethylene, polypropylene, polyolefin, or polyvinyl chloride. In the present invention, when the raw material of polyamic acid is in the form of a solid lump or powder, a bag made of a polymeric material such as polyester or nylon, i.e., a so-called plastic bag, or a paper bag with a polymeric film on the inside may be used. In the case of such a bag-shaped container, the innermost layer of the container is a sealant for heat sealing, so that the contents are in direct contact with the sealant layer.

[0034] The fatty acid compound of the present invention is widely used as an additive to polyethylene, polypropylene, polyolefin, etc., which are used in the inner walls and sealants of containers. If it were possible to use a container whose inner walls are covered with a material that does not contain these, the inclusion of these fatty acid compounds could be eliminated, but in reality, it is difficult to procure such a container.

[0035] In the present invention, even when a container whose inner wall is covered with a material containing the above-mentioned fatty acid compound as an additive is used, if the container is stored under specific conditions, the amount of aliphatic compounds mixed in can be reduced to or below the amount that generates microbubbles. That is, log 10 (day)≦2300×(1 / T)-5.3 (Here, day is the storage time (unit: day), and T is the storage temperature (unit: K).) Within the range of storage temperature and storage time satisfying the above relational expression, the amount of fatty acid-based compounds mixed in can be kept below the limit for the generation of microbubbles, and as a result, a polyimide film can be obtained in which the number of defects with a diameter of 2 μm or more observed by a differential interference microscope is 2 or less per square centimeter, preferably 1 or less per square centimeter, more preferably 1 or less per 10 square centimeters, and even more preferably 1 or less per 100 square centimeters. Storage temperatures and storage times satisfying this relational expression are, for example, 1 month (30 days) at 60°C, 3 months (90 days) at 40°C, and 8 months (240 days) at 25°C. EXAMPLES

[0036] The present invention will be described in more detail below with reference to examples. <Experimental Example 1> Immediately after purification, 1.5 g of each of 5-amino-2-(4-aminophenyl)benzoxazole and pyromellitic dianhydride was weighed out, sealed in a sample bottle together with 12 ml of chloroform, and extracted for 2 hours while ultrasonically dispersing. The extract was filtered, and the filtrate was concentrated to dryness at room temperature under a nitrogen atmosphere, dissolved in deuterated chloroform, and then subjected to 1H-NMR measurement (400 MHz). For quantification, 50 μg of dimethyl isophthalate was added as an internal standard. As a result, at least 0.001 mass% or more of fatty acids having 8 to 30 carbon atoms, fatty acid salts having 8 to 30 carbon atoms, fatty acid amides having 8 to 30 carbon atoms, and fatty acid derivatives having 8 to 30 carbon atoms were not detected in either raw material.

[0037] <Polyamic acid polymerization example> This raw material was used to polymerize polyamic acid. After replacing the atmosphere in a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirring rod with nitrogen, 100 parts by mass of 5-amino-2-(4-aminophenyl)benzoxazole was added to 1400 parts by mass of distilled and purified N,N-dimethylacetamide to completely dissolve it, then 96 parts by mass of pyromellitic dianhydride was added, and a dispersion of colloidal silica dispersed in dimethylacetamide as a lubricant (Nissan Chemical Industries' "Snowtex (registered trademark) DMAC-ST30", but a product delivered within one week from the date of manufacture) was added so that silica (lubricant) was 0.12% by mass of the total polymer solid content in the polyamic acid solution, and the mixture was stirred for 18 hours at a reaction temperature of 25°C to obtain a brown, viscous polyamic acid solution A (polyamic acid composition A). 10 g of this polyamic acid solution was reprecipitated in a large amount of chloroform, and the supernatant was concentrated and dried at room temperature under a nitrogen atmosphere, dissolved in deuterated chloroform, and 1H-NMR measurement (400 MHz) was performed. For quantification, 50 μg of dimethyl isophthalate was added as an internal standard. As a result, at least 0.001 mass% or more of fatty acids having 8 to 30 carbon atoms, fatty acid salts having 8 to 30 carbon atoms, fatty acid amides having 8 to 30 carbon atoms, and fatty acid derivatives having 8 to 30 carbon atoms were not detected. In addition, the reduced viscosity of this polyamic acid was 3.6 dl / g.

[0038] <Polyimide film manufacturing example> The polyamic acid solution A was coated on the non-lubricated side of a polyethylene terephthalate film A-4100 (manufactured by Toyobo Co., Ltd.) using a comma coater, and after drying at 110°C for 5 minutes, the polyamic acid film A was wound up without peeling it off from the support. The amount of the remaining solvent in the film was 39% by mass as measured by TGA. 5 g of this polyamic acid film A was weighed out, sealed in a sample bottle together with 50 ml of chloroform, and extracted for 2 hours while ultrasonically dispersing. The extract was filtered, and the filtrate was concentrated to dryness under a nitrogen atmosphere and dissolved in deuterated chloroform, and then 1H-NMR measurement (400 MHz) was performed. For quantification, 50 μg of dimethyl isophthalate was added as an internal standard. As a result, at least 0.001 mass % or more of fatty acids having 8 to 30 carbon atoms, fatty acid salts having 8 to 30 carbon atoms, fatty acid amides having 8 to 30 carbon atoms, and fatty acid derivatives having 8 to 30 carbon atoms were not detected in the polyamic acid film. The polyamic acid film was passed through a pin tenter having three heat treatment zones, and heat-treated at 150°C for 2 minutes in the first stage, 220°C for 2 minutes in the second stage, and 475°C for 4 minutes in the third stage. Both ends where the pin marks remained were slit to obtain polyimide film A with a width of 700 mm and a thickness of 38 μm, which was then wound into a roll.

[0039] <Counting the number of defects> A 50 mm strip (i.e., a rectangle 50 mm long and 700 mm wide, with the length axis in the film formation direction) was cut out widthwise from a point 10 m away from the outermost circumference of the roll of obtained polyimide film A, and three 50 mm squares were used as observation samples: 100 mm to 150 mm from the left end of the film, 100 mm to 150 mm from the right end of the film, and 25 mm to the left and right of the center of the film. The air side of the observation sample was observed with a differential interference microscope at 100x magnification (field of view approximately 1.5mmφ), and defects of 2μm or more with noticeable color unevenness were counted along with mapping. When the number of defects exceeded 75 (equivalent to 3.0 defects / cm2), it was determined that there were "many defects" and the coefficient was discontinued. The number of defects of 2μm or more was 0.0 defects / cm2. The side that was in contact with the support (polyethylene terephthalate film in this example) during preparation of the polyamic acid film is the substrate side, and the side that faced the air is the air side.

[0040] <Comparative Experiment Example 1> <Storage of raw polyamic acid materials> Immediately after purification, 5-amino-2-(4-aminophenyl)benzoxazole and pyromellitic anhydride were placed in plastic bags with a polyolefin sealant on the inside as containers and stored at 40°C for 60 days. Both were powder raw materials. The distilled and purified N,N-dimethylacetamide was placed in a polyethylene-coated metal can, which was then tightly sealed and stored at 40°C for 60 days. A dispersion obtained by dispersing colloidal silica in dimethylacetamide ("Snowtex (registered trademark) DMAC-ST30" manufactured by Nissan Chemical Industries, Ltd.) that had been delivered within one week of production was similarly placed in a metal can with an inner surface coated with polyethylene as a container, securely sealed, and stored at 40°C for 60 days.

[0041] The raw material stored at 40°C for 60 days was used to carry out polymerization in the same manner as in Experimental Example 1 to obtain polyamic acid solution B. 10 g of this polyamic acid solution B was reprecipitated in a large amount of chloroform, and the supernatant was concentrated to dryness at room temperature under a nitrogen atmosphere, dissolved in deuterated chloroform, and then subjected to 1H-NMR measurement (400 MHz). For quantification, 50 μg of dimethyl isophthalate was added as an internal standard. As a result, 0.12% by mass of erucic acid amide was detected relative to the polyamic acid.

[0042] Analysis of the polyolefin sheet on the inside of the plastic bag used to store the powdered polyamic acid raw material detected 1.5% by mass of erucamide. Similarly, analysis of the polymer film on the inside of the metal can used to store the liquid raw material detected 0.01% by mass of stearic acid. It can be concluded that at least the erucamide contained in Polyamic Acid Solution B originated from the storage container.

[0043] The obtained polyamic acid solution B was used in the same manner as in Experimental Example 1 to obtain a polyimide film B. When the obtained polyimide film B was observed with a differential interference microscope, it was found that there were 3 or more defects of 2 μm or more per square centimeter on the air side. In addition, when a cross section of the defective part of the film was observed, microbubbles with an outer diameter of 1.5 μm to 2 μm were observed in the range of 2 to 8 μm from the air side of the film.

[0044] <Storage experiment> Immediately after purification, 5-amino-2-(4-aminophenyl)benzoxazole and pyromellitic anhydride used in the Comparative Experimental Example were placed in plastic bags with a polyolefin sealant on the inside, as were the containers used in the Comparative Experimental Example, and stored for the storage temperatures and storage times shown in Table 1. Polyimide films were then produced in the same manner as in Experimental Example 1, and defects were observed using a differential interference microscope. The results are shown in Table 1. Here, the number of defects was marked as ◯ when it was 1.0 defect / cm2 or less, △ when it was more than 1.0 defect / cm2 and 2.0 defect / cm2 or less, and × when it was more than 2.0 defect / cm2.

[0045] [Table 1]

[0046] The results of the storage experiment are plotted on the vertical axis as the logarithm of storage time and on the horizontal axis as the reciprocal of storage temperature, and are shown in Figure 1. The dotted diagonal lines in the graph in Figure 1 indicate log 10 (day)=2300×(1 / T)-5.3 It can be seen that polyimide films with a low number of defects can be obtained in the area below this diagonal line. [Industrial Applicability]

[0047] As described above, if the raw materials are stored and managed under the conditions shown in the present invention, a high-quality polyimide film with few defects can be obtained. The polyimide film obtained by the present invention can be suitably used for forming high-quality fine patterns, and is particularly suitable for the backplane of flexible displays, which require the formation of fine TFTs.

Claims

1. The surface has 2 or less defects with a diameter of 2 μm or more per square centimeter as observed by a differential interference microscope, the defective portion having a diameter of 2 μm or more observed by the differential interference microscope is a convex defect resulting from a microbubble present inside the film at the same planar coordinate position, A polyimide film, characterized in that the outer diameter size of the microbubbles, as determined by observation of a cross section of the film in the thickness direction of the film, is 0.1 μm or more and 3 μm or less.

2. 2. The polyimide film according to claim 1, wherein the film thickness is 0.5 μm to 200 μm.

3. 3. The polyimide film according to claim 2, wherein the outer diameter of the microbubbles in the film surface direction is 0.5 μm or more and 5 μm or less.

Citation Information

Patent Citations

  • Low-temperature stable storage method for polyamide acid glue liquid as well as refrigerating liquid composition

    CN103159964A

  • Biological shielding body of nuclear reactor

    JP1982096292A

  • Preparation of heat-resistant polyimide film through gel

    JP1997227697A

  • Preparation of self-supporting polyimide film containing inorganic fine particle

    JP1998251420A

  • Carrier tape for tab

    JP3761030B2